تحليل أثر السياسة السعرية الزراعية وسياسة الدعم الحكومي في إنتاج محصول القمح في العراق للمدة 1993-2019 - الأحبابي، نصيف جاسم محمد; العجيلي، أحمد محمد أحمد (جامعة تكريت - كلية الإدارة والاقتصاد, 2021)
The study aimed to analyze the impact of price policy and government support for wheat crop by using some variables affecting the production of this crop. The study relied mainly on time series data for the period (1993- 2019) using (ARDL) (Autoregressive Distributed Lag Models). The results showed the significance of both the local price and the cultivated area. Whereas. The significance of the global price and the amounts of subsidy provided for the studied crop showed lack. The study reached some conclusions. The most important of which is that the price policy and the subsidy policy are among the important policies as they work to stimulate the process of agricultural development in Iraq. And because of its positive impact on increasing the growth rate of the studied crop. due to its response to the changes in support prices. The study ended with some recommendations. The most important of which is the necessity of coordination between the price policy and the subsidy policy. Because of its impact on increasing agricultural production of agricultural crops in general and the crop of wheat in particular.
هدفت الدراسة إلى تحليل أثر السياسة السعرية الزراعية والدعم الحكومي لمحصول القمح من خلال استخدام بعض المتغيرات التي تؤثر على إنتاج هذا المحصول، واعتمدت الدراسة بصورة أساسية على بيانات السلسلة الزمنية للمدة (1993 -2019) باستخدام أنموذج ) ARDL) (Autoregressive Distributed Lag Models)، وبينت النتائج معنوية كل من السعر المحلي والمساحة المزروعة، في حين أظهرت عدم معنوية السعر العالمي ومبالغ الدعم المقدمة للمحصول المدروس، وتوصلت الدراسة إلى بعض الاستنتاجات أهمها أن السياسة السعرية الزراعية وسياسة الدعم من السياسات المهمة كونها تعمل على تحفيز عملية التنمية الزراعية في العراق، ولما لها من إثر إيجابي في زيادة معدل نمو المحصول المدروس، بسبب استجابته للتغيرات الحاصلة في أسعار الدعم. وانتهت الدراسة ببعض التوصيات أهمها ضرورة التنسيق بين السياسة السعرية الزراعية وسياسة الدعم، لما لها من أثر على زيادة الإنتاج الزراعي من المحاصيل الزراعية بشكل عام ومحصول القمح بشكل خاص.
Keywords: الإنتاج الزراعية -- المواد الغذائية -- زراعة القمح -- السياسات السعرية -- العراق